PELATIHAN PEMBUATAN COOKIES MADU ZINC “CODUZINC” SEBAGAI ALTERNATIF PEMANFAATAN MADU DI KAMPUNG MADU DESA BRINGIN - Safi'i, Hilma Ayunda; arif budiman, frenky (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Purworejo Hamlet, Bringin Village or better known as Honey Village is located in Badas District. One of the people's livelihoods is as a honey beekeeper. But unfortunately the honey produced by the community has not been utilized optimally, only used as personal consumption and sold in the form of pure honey. From the problems that arise, alternatives are arranged to solve the problem. Furthermore, the alternative was carried out by conducting training in making cookies with PKK mothers and utilizing honey produced by the community. This training also increases the knowledge and skills of PKK mothers regarding the use of honey into other products that are more useful and have more selling value. High interest from partners has a positive impact on the implementation of the program. The output that has been achieved from this training activity is in the form of cookies products that are given additional honey and zinc or named CODUZINC "Zinc Honey Cookies" produced by PKK mothers in Purworejo hamlet, Badas District, Kediri Regency and is expected to help in overcoming stunting problems.